Adolescents with a Disposition toward Compulsive Sexual Behavior: The Role of Shame in Willingness to Seek Help and Treatment. Issue 1 (2nd January 2018) - Efrati, Yaniv
ABSTRACT: The purpose of this study was to examine the relation between shame and religiosity in secular and religious adolescents' willingness to seek help or therapy for their compulsive sexual behavior (CSB). The study population included 274 adolescents (131 boys and 143 girls), aged 14–18 (M = 16.84, SD = 1.29). By religiosity, 51.4% (n = 141) self-defined themselves as secular and 48.6% (n = 133) as religious. Questionnaires were uploaded to Qualtrics—an online platform for questionnaires. Help-seeking steps were prompted by shame. Adolescents who experienced a high degree of shame with their CSB reported greater willingness to receive help; those who reported little or no shame did not express a desire to seek help, despite their level of CSB. Among secular adolescents, but not among religious ones, shame motivated help seeking and willingness to receive help. Religious adolescents refrain from seeking help despite their shame of their CSB.